Decentralized Oil Production in Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The intermediate Technology Zimbabwe (ITZ) decentralized oil project is an example of a successful small-scale food processing enterprise. In the past, all cooking oil in Zimbabwe has been supplied by four main producers using a solvent extraction...